The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1519-566x2008000500006
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of immature stages in the neotropical nonfrugivorous Tephritinae Fruit Fly Species Rachiptera limbata Bigot (Diptera: Tephritidae) on Baccharis linearis (R. et Pav.) (Asteraceae)

Abstract: Neotropical Entomology 37(5): 536-545 (2008) Morfologia dos Estados Imaturos da Espécie de Mosca das Frutas Neotropical não Frugívoradobras da cutícula, as margens da abertura oral, o esqueleto cefalofaríngeo, os espiráculos anterior e posterior e os lóbulos anais das larvas de primeiro, segundo, terceiro estádios e da pupa. O esqueleto cefalofaríngeo é altamente esclerotizado e apresenta um orifício ou abertura na cornua ventral, característica essa que parece ser plesiomórfi ca em R. limbata e outras esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In their description of the third-instar larvae of members of the Ceratitis FAR complex, Steck and Ekesi (2015) relied on electron microscope images, which are not practical for use in a routine diagnostic laboratory. Frías et al (2006 , 2008 ) also used electron microscope images to visualise some characteristics. The multi-entry key published by Carroll et al (2004 onwards) uses a combination of characteristics that can be observed using a dissection microscope, slides prepared for visualising using a compound microscope and slides prepared to visualise using scanning electron microscopy (SEM).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their description of the third-instar larvae of members of the Ceratitis FAR complex, Steck and Ekesi (2015) relied on electron microscope images, which are not practical for use in a routine diagnostic laboratory. Frías et al (2006 , 2008 ) also used electron microscope images to visualise some characteristics. The multi-entry key published by Carroll et al (2004 onwards) uses a combination of characteristics that can be observed using a dissection microscope, slides prepared for visualising using a compound microscope and slides prepared to visualise using scanning electron microscopy (SEM).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Region of interest circled. Abbreviations used in LucID key: AT = Apical Tooth; DA = Dorsal Apodeme; DS = Dental Sclerite; MD = Mandible; MN = Mandibular Neck; PT = Preapical Tooth; VA = Ventral Apodeme (from: Frías et al 2006 ).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…5) The egg of P. trinotata is similar to those of the four species for which the egg has been described previously, P. culta (Wiedemann), P. cultaris (Coquillett), P. forficula Benjamin, and P. gentilis Hering (Benjamin 1934, Cavender & Goeden 1984, in having an elongate, slender lobe on the micropyle end. The lobe is absent in Rachiptera limbata Bigot (Frías 2008) suggesting that it is a synapomorphy of Paracantha species, although it should also be noted that clearly unrelated tephritid species such as Aciurina ferruginea (Doane) and some species of Chaetorellia and Craspedoxantha have a similar elongate lobe on the egg (Tauber & Tauber 1967, White & Marquardt 1989, Freidberg 1985. 6) Paracantha species, except P. trinotata, have a radiate wing pattern, with at least some of the rays broad and orange with dark borders (Figs.…”
Section: Oedicarena Beamerimentioning
confidence: 99%
“…Most species form an unusual gall (Fig. 104) that is surrounded by a white spongy substance secreted by the larva giving it the superficial appearance of a ball of styrofoam (Aljaro et al 1984, Frías 2008.…”
Section: Pyrgotoides Curranmentioning
confidence: 99%